Aquaglyceroporins: Drug Targets for Metabolic Diseases? - Calamita, Giuseppe; Perret, Jason; Delporte, Christine (Frontiers in Physiology, 2018)
Aquaporins (AQPs) are a family of transmembrane channel proteins facilitating the transport of water, small solutes, and gases across biological membranes. AQPs are expressed in all tissues and ensure multiple roles under normal and pathophysiological conditions. Aquaglyceroporins are a subfamily of AQPs permeable to glycerol in addition to water and participate thereby to energy metabolism. This review focalizes on the present knowledge of the expression, regulation and physiological roles of AQPs in adipose tissue, liver and endocrine pancreas, that are involved in energy metabolism. In addition, the review aims at summarizing the involvement of AQPs in metabolic disorders, such as obesity, diabetes and liver diseases. Finally, challenges and recent advances related to pharmacological modulation of AQPs expression and function to control and treat metabolic diseases are discussed.